Fine Mapping of Loci on BTA2 and BTA26 Associated with Bovine Viral Diarrhea Persistent Infection and Linked with Bovine Respiratory Disease in Cattle - Zanella, Ricardo; Casas, Eduardo; Snowder, Gary; Neibergs, Holly L. (Frontiers in Genetics, 2011)
Bovine respiratory disease (BRD) is considered to be the most costly infectious disease in the cattle industry. Bovine viral diarrhea virus (BVDV) is one of the pathogens involved with the BRD complex of disease. Bovine viral diarrhea virus infection also negatively impacts cow reproduction and calf performance. Loci associated with persistently infected animals (BVD-PI) and linked with BRD have previously been identified near 14 Mb on bovine chromosome 2 (BTA2) and 15.3 Mb on bovine chromosome 26 (BTA26). The objective of this study was to refine the loci associated with BVD-PIand linked with BRD. Association testing for BVD-PI was performed on a population of 65 BVD-PI calves, 51 of their dams, and 60 unaffected calves (controls) with 175 single nucleotide polymorphisms (SNPs) on BTA2 and 209 SNPs on BTA26. Comparisons were made between BVD-PI calves and controls calves and the dams of BVD-PI calves and controls calves. For the linkage analysis of BRD, the same markers were used to genotype 2 half sib-families consisting of the sires and 72 BRD positive and 148 BRD negative offspring. Using an allelic chi-square test, 11 loci on BTA2 and 8 loci on BTA26 were associated with the dams of the BVD-PI calves (P < 0.05) and 5 loci on BTA2 and 10 loci on BTA26 were associated with BVD-PI calves. One locus on BTA2 and two loci on BTA26 were found to be linked (P < 0.05) with BRD. These results further refined the loci associated and linked with BVD-PI and BRD, respectively.